An Experimental Study on Task-Oriented Motor Practice on Aerobic Capacity, Risk of Fall and Quality of Life in Elderly Population - Paul, Mantu; Sarma, Binod Chandra (Journal of Neonatal Surgery, 2025)
Background of the study: Aging is defined as “a persistent decline in the age-specific fitness components of an organism due to internal physiological degeneration.” proper balance is needed during the most activities of daily life. A reduction in balancing ability is one of the factors that adversely affect the ADL and QOL of elderly population. The balance control is a complex process which requires the coordination of the sensory, musculoskeletal and nervous systems. Furthermore, producing corrective movement for balance demands adequate musculoskeletal functions as well. Studies examining age-related changes of balance control showed that sway during quiet stance begins to increase approximately at the age of fifty (2). With the increase of ageing population, improving of the elderly adults’ balance control is becoming more and more important. Subjects and Methods: 30 elderly persons were divided into two groups: intervention group (n=15) and control group (n=15). Methodology: Task-Oriented Motor Practice, 8 weeks; 3 sessions per week, 1 hours/session once a day Results: The task-oriented activities promoted hand function (coordination). Conclusion: Initially task-oriented motor practice was used only in neurological rehabilitation. In the recent years this therapeutic approach was applied among elderly population as well. Our results showed that task-oriented motor practice might be an acceptable, safe and effective type of exercise program for even community-living elderly adults to maintain and improve their functional abilities.